Exporting Financial Services in Latin America and the Caribbean - Gonzalez, Adrian F.; Lopez-Rocha, Silvia Carolina; Yang, Rongpeng; Youbi, Marilyne; Zabalbeitia-Mugica, Ines (World Bank, Washington, DC, 2019)
According to the World Trade Organization (WTO), trade in services has become the most dynamic segment of world trade, growing more quickly than trade in goods. While travel remains the most exported service both worldwide and in Latin America and the Caribbean (LAC), other services are becoming relevant for both developed and developing economies. Among them, financial services is one of the most important categories in terms of value. Worldwide, the value of financial services exports rose in real terms between 2008 and 2017. Nevertheless, this global trend of rising exports of financial services was not reflected in LAC, where they contracted between 2008 and 2016. The economies of Latin America and the Caribbean have significant potential to export financial services. To take advantage of this opportunity, governments in the region can work on a variety of fronts to raise their economies’ competitiveness in this area. Two specific challenges are the availability of human capital and electronic infrastructure. The former refers to the limited number of professionals that, in addition to Spanish, speak the language of the importing economies and are adequately educated and experienced in the areas associated with services exports. The latter refers to the electronic infrastructure and digital systems that facilitate the export of financial services, but also the high cost to develop communication schemes in the region. Consequently, LAC’s export dynamism in financial services will depend on long-term public policies and public-private strategies with clear objectives for promoting human capital and a competitive digital ecosystem.